Evaluation of Implementation of Public Elementary School Regrouping Policy in South Jakarta Region - Harianto, Aryono Fajar; Fuad, Nurhattati; Sugiarto, Sugiarto (Universitas Malikussaleh, 2020)
This study aims to obtain factual information regarding the implementation of the policy of merging public elementary schools in the South Jakarta region which consists of SDN Rawajati 03, SDN Pondok Pinang 10, and SDN Pejaten Timur 11. The method used in this study is evaluative with data collection techniques using interviews, observation, and documentation. Subjects in the study are the Principal, Teachers, and School Operators. The research findings show that the school incorporation policy is very precisely implemented which is seen from three perspectives of school managers who are research subjects. Based on the principal's perspective, it is known that the school incorporation policy has an impact on school management that is more effective and efficient so that education can run smoothly. The school incorporation policy also makes teachers work together and discuss related learning strategies so that students become more effective in learning and teaching activities. Different results were found from the perspective of school operators, namely the implementation of the school merger policy resulting in the increasing workload of school operators.